An analysis of the energy flow and energy potential from human energy harvesting with a focus on walking. Issue 1 (31st December 2016) - Partridge, J.S.; Bucknall, R.W.G.
Abstract: This paper aims to determine the limitations for electrical energy generation from harvesting mechanical work during walking. The assessment was considered from the point of chemical energy ingested in food, through the development of mechanical work, to the conversion into useful electrical energy from the perspective of the conversion efficiencies. An average person was considered, with four mechanical to electrical energy conversion technologies assessed. It was found that for an individual walking on level ground a potential of up to 5 J/step of electrical energy is available. Stair use impacts this, where stair ascent decreased and descent increased the potential. It was concluded that, although the energy outputs are small, they scale with the number of people, where an estimated potential of 900 MWh/day is calculated in the UK. Harvesting even a fraction of this available potential would appear worthwhile, however, it is unclear if this potential can be practically utilised.